Financial liberalization, market structure and credit penetration - Balmaceda, Felipe; Fischer, Ronald D.; Ramirez, Felipe (Journal of Financial Intermediation, 2014)
This paper shows that the effects of financial liberalization on the credit market of a small and capital constrained economy depend on the market structure of domestic banks prior to liberalization. Specifically, under perfect competition in the domestic credit market prior to liberalization, liberalization leads to lower domestic interest rates, in turn leading to increased credit penetration. However, when the initial market structure is one of imperfect competition, liberalization can lead to the exclusion of less wealthy entrepreneurs from the credit market. This provides a rationale for the mixed empirical evidence concerning the effects of liberalization on access to credit in developing markets. Moreover, the analysis provides new insights into the consequences of foreign lenders’ entry into developing economies.